SINTESIS DAN KARAKTERISASI SENYAWA OKSOTRINUKLIR [Ru2Co(O)(OOCCH3)6(C5H5N)3](ClO4) - Aldes Lesbani; Risfidian Mohadi; Nurlisa Hidayati (Jurnal Kimia (Journal of Chemistry), 2012)
The oxotrinuclear compound [Ru2Co(O)(OOCCH3)6(C5H5N)3](ClO4) has been synthesized using RuCl3?nH2O at room temperature under oxygen atmospheric condition. The oxotrinuclear complex was characterized by FT-IR spectrophotometer and mass spectrometer with cold spray ionization (CSI) method. The FT-IR spectra of the resulted oxotrinuclear compound show has specific vibration at 692 cm-1. This absorption is related to M3O vibration (M= metal). CSI-mass spectra of the oxotrinuclear compound show that pyridine as ligand was fragmented in oxotrinuclear compound.